Bidding in fixed rate tenders: Theory and experience with the ECB tenders - Tuomas Välimäki (Bank of Finland, 2002)
This paper presents a model of the optimal bidding behaviour of a single bank in the context of fixed rate liquidity tenders.Banks' bidding is shown to depend crucially on the central bank's liquidity policy as regards tender allotments.The paper also analyses ECB liquidity policy in terms of the model.The ECB, while applying fixed rate tenders, appears to have been attempting stabilise the market interest rate at a level close to the main refinancing rate.However, this aim was at least partially overridden by that of stabilising total money market liquidity over the course of the reserve maintenance period - even more so when banks were expecting the ECB to raise the main refinancing rate in the near future.The banks' aggregate bids increased considerably during the period of fixed rate tenders.This was seen to result mainly from profit opportunities associated with a positive spread between market interest rate and main refinancing rate.The positive spread resulted from the combination of expectations of an interest rate hike and liquidity-oriented allotment policy.
URN:NBN:fi:bof-20140807162
Keywords: 330; bidding; money market tenders; liquidity policy; central bank operating framework